Analysis of radiological indicators in the process of environmental certification of the Chornobyl exclusion zone territory - Azarov, Ivan; Zaduna, Oleksiy (Lviv Politechnic Publishing House, 2018)
The problematic issue of environmental certification of radiation hazardous objects that needs to be solved for substantial improvement of the situation in the field of environmental protection, preservation and restoration of natural systems and ecosystems is worked out. The purpose of the development of the environmental passport of the Chornobyl Exclusion Zone (CEZ) territory is defined. The requirements and recommendations for the structure and content of the environmental passport of the CEZ are provided.
Keywords: environmental passport; radiation hazardous object; environment protection; natural resources